The Effect of Water Quality Testing on Household Behavior: Evidence from an Experiment in Rural India - Hamoudi, Amar (The American Society of Tropical Medicine and Hygiene, 2012)
How does specific information about contamination in a household's drinking water affect water handling behavior? We randomly split a sample of households in rural Andhra Pradesh, India. The treatment group observed a contamination test of the drinking water in their own household storage vessel; while they were waiting for their results, they were also provided with a list of actions that they could take to remedy contamination if they tested positive. The control group received no test or guidance. The drinking water of nearly 90% of tested households showed evidence of contamination by fecal bacteria. They reacted by purchasing more of their water from commercial sources but not by making more time-intensive adjustments. Providing salient evidence of risk increases demand for commercial clean water.